Parent Guardian Participation In Supporting Pondok Programs At Darul Husaini Nahdatul Wathan Diniyah Islamiyah Islamic Boarding School, Sanggeng, Kelebuh Village, Central Praya District - Abd Quddus Al Badani; Baiq Riskika Dewi (Journal of Islamic Religious Studies, 2025)
This study investigates the forms and extent of parental (wali santri) participation in supporting the programs of Pondok Pesantren Darul Husaini NWDI Sanggeng, and examines how such participation contributes to the institution’s success and development. Using a qualitative approach, data were obtained through in-depth interviews, participant observation, and documentation analysis. The results reveal three primary forms of participation: intellectual contribution, material support, and direct involvement in pesantren activities. Intellectual contributions include providing constructive input on institutional policies and program planning. Material support is reflected in financial assistance for operational needs and program implementation. Direct involvement encompasses participation in religious events, community service, and other pesantren-led initiatives. Factors that foster participation include strong trust in the pesantren’s leadership, a high awareness of the importance of religious education, and effective communication between the institution and parents. Conversely, obstacles to participation arise from time constraints due to work commitments, limited financial capacity, and insufficient access to information about ongoing programs. The findings underscore that active parental involvement significantly enhances the quality and sustainability of the pesantren’s educational and character-building efforts. Strengthening communication strategies, fostering mutual trust, and creating more accessible opportunities for involvement are essential to further maximize the role of parents in pesantren development.